DAMPAK KOMPETENSI DAN DUKUNGAN LINGKUNGAN KERJA TERHADAP EFEKTIFITAS PELATIHAN GOOD MANUFACTURING PRACTICES (GMP)DI PT SALIM IVOMAS PRATAMA TBK - Rakhman Roebidin; Aris Wijayanto (Universitas Mercu Buana, 2015)
Abstract. GMP is a mandatory training for implementation of Food Safety in theproduction process. Effectiveness of GMP training is a barometer of success indeveloping human resources through training. Competency and work environmentsupports will make the GMP training more effective for the company. Objective ofresearch to prove competence and work environment support influence theeffectiveness of GMP training at company. The model used to analyze data in thisresearch is multiple linear regression analysis by using variables are Competency (X1),Work environment support (X2) and Effectiveness of GMP training (Y). The study‟spopulation was 102 operators in refeinery PT SIMP Tbk. Based on the results thatcompetency had negative effect no significantly to the effectiveness of GMP training,then work environments support had positive effect significantly to the effectivenessof the GMP training, while another result of analysis for respondents in the age groupover 35 years old and working more than 2 years showed that competence hadnegative effect significantly to the effectiveness of GMP training as well as workenvironment support had positive effect significantly to the effectiveness of GMPtraining.Keywords: Competency, Work Environment Support, Effectiveness of Training, GoodManufacturing Practices (GMP)